A study of the influence of calcium acetate on the process of sunflower oil degumming - Demydova, A. O.; Ghladkyj, F. F.; Aksonova, O. F.; Molchenko, S. M. (Oles Honchar Dnipro National University, 2022)
The stage of degumming of vegetable oils is carried out in order to extract polar lipids – phospholipids. The efficiency of this stage depends not only on the low final content of phospholipids in the refined oil, but also on the safety of the used degumming agents, speed, easiness of degumming and low cost of the process. The process of degumming of sunflower oil in the presence of a new degumming agent - calcium acetate has been studied. Calcium acetate (food additive E 263) is a safe substance that is completely absorbed by the human body and does not have a negative impact on the environment. Rational conditions for degumming to obtain the oil with a phospholipid content of ˂ 0.05% have been established. Rational conditions for degumming in the presence of calcium acetate have been determined. The main indicators of the quality of refined oil and lecithin obtained as a result of degumming have been investigated. They comply with the requirements of the current regulatory documents. One of the disadvantages of sunflower lecithin is its ability to be changed from a liquid to a plastic state, namely, to increase the viscosity during storage. The double technological effect of using calcium acetate has been proven – it is an effective degumming agent and an additive, is able to significantly reduce the viscosity of lecithins, obtained at the hydration stage, to the values at which they do not form plastic modification.
Дослідження впливу ацетату кальцію на процес гідратування соняшникової олії
Стадія гідратування рослинних олій проводиться з метою вилучення полярних ліпідів – фосфоліпідів. Ефективність проведення цієї стадії полягає не лише в низькому остаточному вмісті фосфоліпідів у гідратованій олії, а й у безпечності застосованих гідратуючих агентів, швидкості, простоті проведення гідратування та низькій вартості процесу. Досліджено процес гідратування соняшникової олії в присутності нового гідратуючого агенту – ацетату кальцію. Ацетат кальцію (харчова добавка Е 263) є безпечною речовиною, що повністю засвоюється організмом людини та не чинить негативного впливу на довкілля. Встановлено раціональні умови проведення гідратування з метою одержання олії зі вмістом фосфоліпідів ˂ 0.05 %, а саме: кількість ацетату кальцію – 0.01 %;тривалість гідратування – 10 хв; кількість води – 1 %. Визначено раціональні умови проведення гідратування в присутності ацетату кальцію. Досліджено основні показники якості гідратованої олії та лецитину, одержаного в результаті гідратування. Вони відповідають вимогам діючих нормативних документів. Одним з недоліків лецитину соняшнику є його здатність переходити з рідкого стану до пластичного, тобто підвищувати в’язкість в процесі зберігання. Доведений подвійний технологічний ефект використання ацетату кальцію – як ефективного гідратаційного агенту та добавки, що суттєво знижує в’язкість лецитинів (які одержують на стадії гідратування) до значень, за яких вони не утворюють пластичної модифікації.
Keywords: sunflower oil; degumming; lecithin; phosphatide concentrate; phospholipid content; lecithin viscosity; calcium acetate; соняшникова олія; соняшникова олія; лецитин; фосфатидний концентрат; вміст фосфоліпідів; в'язкість лецитину; ацетат кальцію